Revisiting the Intermolecular Fujiwara Hydroarylation of Alkynes. Issue 13 (6th April 2017) - Godoi, Marla N.; de Azambuja, Francisco; Martinez, Pablo David G.; Morgon, Nelson H.; Santos, Vanessa G.; Regiani, Thaís; Lesage, Denis; Dossmann, Heloise; Cole, Richard B.; Eberlin, Marcos N.; Correia, Carlos Roque D.
Abstract : The Fujiwara hydroarylation of alkynes was reinvestigated using the addition of indole to methyl or ethyl phenylpropiolate catalyzed by Pd(OAc)2 as a model reaction. Reactions were monitored by both 1 H NMR spectroscopy and electrospray ionization mass spectrometry (ESI/MS), and also through reactions carried out in the gas phase using MS/MS experiments. Contrary to the original suggestion for exclusive heteroarene activation, the data supports the coexistence of both heteroarene activation (C–H activation) and alkyne activation (Friedel–Crafts‐type pathway). Under the reaction conditions used in this work, intermediates for both mechanisms were detected by NMR spectroscopy and MS, but alkyne activation seems to be predominant according to 1 H NMR spectroscopic studies and theoretical predictions. Alkyne activation is promoted by the coordination of an electrophilic palladium species to the C–C triple bond, followed by nucleophilic attack of the heteroaryl counterpart. Two previously undetected equilibria in this reaction involving the vinylpalladium intermediates and the final products were also found to be critical to the stereoselectivity of the reaction. Abstract : The Fujiwara hydroarylation of alkynes was reinvestigated. Reactions were monitored by 1 H NMR spectroscopy, by electrospray ionization mass spectrometry (ESI/MS), and through reactions carried out in the gas phase using MS/MS experiments.